Changes in attitudes towards gender norms following childbirth - Van der Velde, Lucas (Leibniz Institute for East and Southeast European Studies, IOS, 2022)
While the increase in the gender wage gap following childbirth is well-documented in the literature much less is known about what stands behind this development. This research focuses on one possible channel: changes in attitudes towards gender roles. Using longitudinal data from several European countries, I show that respondents tend to adopt more conservative views following childbearing, particularly in the case of the importance of having a child, and whether men should have priority when jobs are scarce. Moreover, the relation appears to be driven by respondents in countries where women shoulder a bigger share of household chores, and where less formal care is available.
10419/267512
Keywords: Graue Literatur; Demographie; Bevölkerungsentwicklung; Geburtenentwicklung; Geschlechterrolle; Gleichberechtigung; Frau; Geschlecht; Soziale Norm; Konservativismus; Umfrage; Vergleich; gender norms; child-birth; cross-country comparison; institutions